American Mainstream Massmedia in the Service of US Global National Foreign Policy Interests: Preparation of American and World Public for Acceptance and Justification of Coercive and War Policy - Nikoliš, Dušan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
Even in modern sophisticated digital and satellite age of direct and instant, in real time, TV news coverage, american global mainstream electronic and press massmedia are havily influenced, shaped and determined by the crucial US global national foreign policy and military security interests, goals and priorities, particularly in the case of news, reports, information and facts about events in international and foreign policy affairs. By this, US foreign policy and military-security establishment controls American and a good part of the world public opinion, shapes collective values, social mentality, mind, conscience and spirit of the American people, making American mass media a servant of the establishment. Otherwise, if it were not like that, it would not be possible to have such a huge snowball of one-way, one-sided, untrue and false reports in US media about some international events (crises, civil wars, military interventions, aggressions) in the past twenty years in which the USA participated as the leading actor. In order to approach and penetrate the American public, traditionally indifferent to international events, world news and reports must be adapted, brought closer to local conditions and "localised" with them. Namely, "translated" to domestic, local social mentality and value system, identified with it, which is the only way for news to be sold in the US info-media market. This process is clearly seen and proved in the American mainstream mass media approach in the civil war in Bosnia and Herzegovina in the 90-ties where events and facts were subject to intentional and planned distortion and misinterpretation, and where objective information and reports gave way to foreign policy propaganda, becoming propaganda itself.